2018
DOI: 10.3390/ijms19071893
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Role of PPARβ/δ in NAFLD

Abstract: Non-alcoholic fatty liver disease (NAFLD) is a major health issue in developed countries. Although usually associated with obesity, NAFLD is also diagnosed in individuals with low body mass index (BMI) values, especially in Asia. NAFLD can progress from steatosis to non-alcoholic steatohepatitis (NASH), which is characterized by liver damage and inflammation, leading to cirrhosis and hepatocellular carcinoma (HCC). NAFLD development can be induced by lipid metabolism alterations; imbalances of pro- and anti-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 172 publications
(226 reference statements)
1
41
0
Order By: Relevance
“…The effectiveness of agonists for PPAR-α/δ has been confirmed in NASH patients as well[ 166 ]. Thus, the application of PPAR agonists, notably those for PPAR-β/δ isoforms, appears to be promising therapeutics for the treatment of NAFLD[ 167 ]. While the molecular mechanisms for how PPAR-β/δ controls insulin signaling are largely unknown, a stable interaction of PPAR-β/δ with nuclear T-cell protein tyrosine phosphatase 45 (TCPTP45) isoform has been demonstrated as the most upstream component that resolves the downregulation of insulin signaling[ 168 ].…”
Section: Non-alcoholic Fatty Liver Disease As a Representative Injurymentioning
confidence: 99%
“…The effectiveness of agonists for PPAR-α/δ has been confirmed in NASH patients as well[ 166 ]. Thus, the application of PPAR agonists, notably those for PPAR-β/δ isoforms, appears to be promising therapeutics for the treatment of NAFLD[ 167 ]. While the molecular mechanisms for how PPAR-β/δ controls insulin signaling are largely unknown, a stable interaction of PPAR-β/δ with nuclear T-cell protein tyrosine phosphatase 45 (TCPTP45) isoform has been demonstrated as the most upstream component that resolves the downregulation of insulin signaling[ 168 ].…”
Section: Non-alcoholic Fatty Liver Disease As a Representative Injurymentioning
confidence: 99%
“…The results indicated that HWL‐088 has moderate agonistic activity on PPARδ, exhibiting high selectivity for PPARδ over PPARα and PPARγ. PPARδ activation produces multiple pharmacological effects, such as insulin sensibilization, adipocyte differentiation, anti‐inflammatory and lipid metabolism (Chen, Montagner, Tan, & Wahli, ; Lee et al, ; Luquet et al, ; Palomer et al, ). Moreover, the activation of PPARδ protects β‐cells from apoptosis (Daoudi et al, ), up‐regulating GLP‐1 receptor (Yang et al, ) and increasing mitochondrial function in β‐cells (Tang et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…These unique pharmacological effects might be attributed to the dual potencies of HWL‐088 by simultaneous activation of FFAR1 and PPARδ. Indeed, PPARδ play a key role in insulin sensibilization and lipid regulation, which could act synergistic effects with FFAR1 in glucose and lipid metabolism (Chen et al, ; Luquet et al, ; Palomer et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…These salutary PPAR-δ functions in normal cells are thought to protect against metabolic-syndrome-related diseases, such as obesity, dyslipidemia, insulin resistance, hepatosteatosis, and atherosclerosis [ 44 , 45 ]. Therefore, highly selective synthetic PPAR-δ agonists (e.g., GW0742 [ 46 ], GW501516 [ 35 ]) were developed and tested clinically.…”
Section: Metabolic Regulation By Ppar-δmentioning
confidence: 99%